Legal Recognition of Same-Sex Couples in Poland (Discourse of Law and Administration, 2026)
Poland is one of the few European states that lack any legal recognition of same-sex couples, which is contrary to the standards of the European Court of Human Rights, as decided in the case Przybyszewska and others v. Poland. The aim of the article is to analyse the reasons for this situation as well as the legal aspects of this issue. The starting point for the deliberations will be the European standard on same-sex couples. Then the article will examine, whether the Polish law, especially the Constitution, permits the formal recognition of same-sex couples. Lastly, the article will focus on legal consequences of the lack of recognition of same-sex couples, with reference to parental rights and childcare, inheritance rights, taxation and other issues.
Keywords: same-sex couples; right to family and private life; non-discrimination; children’s rights